2019
DOI: 10.3390/resources8040157
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of Total Soil Carbon Stocks in the Contiguous United States Based on the Avoided Social Cost of Carbon Emissions

Abstract: Total soil carbon (TSC) is a composite (total) stock, which is the sum of soil organic carbon (SOC) and soil inorganic carbon (SIC). Total soil carbon, and its individual two components, are all important criteria for assessing ecosytems services (ES) and for achieving United Nations (UN) Sustainable Development Goals (SDGs). The objective of this study was to assess the value of TSC stocks, based on the concept of the avoided social cost of carbon dioxide emissions, for the contiguous United States (U.S.) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…It also can be used to analyze the patterns of value for regulating ES. Mikhailova et al (2019) [35] provided a valuation of soil organic carbon (SOC) stocks in the contiguous U.S. based on taxonomic pedodiversity and the avoided social cost of carbon (SC-CO 2 ) emissions, which varied by the degree of soil weathering as indicated by soil order information. This study found the following distribution of SC-CO 2 contribution within the contiguous U.S.: slightly-weathered soils (38%), intermediately-weathered soil (51%), and strongly-weathered soils (11%).…”
Section: Total Economic Value (Tev)mentioning
confidence: 99%
See 2 more Smart Citations
“…It also can be used to analyze the patterns of value for regulating ES. Mikhailova et al (2019) [35] provided a valuation of soil organic carbon (SOC) stocks in the contiguous U.S. based on taxonomic pedodiversity and the avoided social cost of carbon (SC-CO 2 ) emissions, which varied by the degree of soil weathering as indicated by soil order information. This study found the following distribution of SC-CO 2 contribution within the contiguous U.S.: slightly-weathered soils (38%), intermediately-weathered soil (51%), and strongly-weathered soils (11%).…”
Section: Total Economic Value (Tev)mentioning
confidence: 99%
“…This study found the following distribution of SC-CO 2 contribution within the contiguous U.S.: slightly-weathered soils (38%), intermediately-weathered soil (51%), and strongly-weathered soils (11%). In another example, according to Mikhailova et al (2019) [36], Mollisols have the highest total soil carbon (TSC, soil organic + soil inorganic carbon) storage midpoint value ($7.78T) based on the social cost of carbon (SC-CO 2 ) and avoided emissions provided by carbon sequestration, which is about 30% of the total midpoint value for the contiguous U.S. These types of analyses are useful in identifying soil "hotspots" with regards to various ES/ED applications at different scales which has the potential to be managed with precision agriculture [2,37].…”
Section: Total Economic Value (Tev)mentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses allowed estimation of potential social costs of soil carbon, which is useful for decision-making at the national level using detailed tables and maps of social costs of C showing areas with high soil C content, which can become "soil carbon hotspots" upon disturbance [10]. At the national level, the analysis showed that states have different types of soils with various soil C types (e.g., Maryland is dominated by SOC, state of New Mexico is dominated by SIC) [11], which requires soiland carbon-specific management strategies. Some states demonstrated more soil variability compared to others.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the monetary valuation of social costs and avoided social costs also depends on the user, goal, scale of the assessment, and the available data (e.g., soil survey databases, intensive field soil sampling data, etc.). For example, Mikhailova et al (2019aMikhailova et al ( , 2019b and Groshans et al (2019), reported monetary values of the avoided social cost of CO 2 emissions from SOC, SIC, and TSC stocks in the contiguous United States by soil order, soil depth, land resource region, state, and region based on data from Guo et al (2006). This type of assessment, using information from the State Soil Geographic (STATSGO) database, has a great degree of generalization which is suitable for country-level valuation but it is of limited application at the field or farm scales.…”
Section: Introductionmentioning
confidence: 99%